Strategi Cause Related Marketing Bisnis dan Keberkahan Perspektif Islam - Sulistyowati, Sulistyowati; Kurniawati, Siti Ria (Lembaga Pengembangan Kinerja Dosen, 2025)
This research examines the concept of Cause Related Marketing (CRM) from an Islamic perspective, focusing on barakah (blessing) as spiritual added value. Through systematic literature review, the study analyzes Islamic business ethics principles underlying CRM, such as maslahah (public interest), amanah (trustworthiness), and ihsan (excellence). The findings demonstrate that CRM within an Islamic framework contributes significantly to developing sustainable business models that are not only profit-oriented but also create positive social value. The implementation of CRM in companies like Wardah Cosmetics proves that integrating Islamic values into marketing strategies can generate blessings reflected in consumer trust, brand loyalty, and sustainable social impact. This research also identifies challenges in implementing Islamic-based CRM, including maintaining sincerity, transparency, and accountability. Educational institutions and religious scholars play crucial roles in raising awareness and guiding CRM practices that align with sharia principles to obtain business blessings.